Studi Literatur Peran Kepemimpinan Dalam Perubahan dan Perkembangan Organisasi - Muhammad Anshari Hutasuhut; Nuri Aslami (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
One of the factors influencing an organization's performance is its leadership, particularly when it comes to implementing change. It is preferable to first understand what the term leader means in order to comprehend what is meant by leadership (leadership) (leader). This is so that a leader, who performs the task of performing the leadership action, can exercise leadership. This study combines qualitative research methodologies with strategies for analyzing literature reviews. The following describes transformative leadership. (1) According to Bass, charisma, charismatic influence, or idealized influence, is an emotional aspect of leadership that typically refers to the strength of the leader who is able to have a significant influence on his followers. (2) Leadership that inspires and encourages people to accomplish goals is known as inspiring motivating. (3) By encouraging "issue awareness and problem solutions," the leader stimulates the intellect of his followers. (4) Individual consideration, specifically the leader using individual considerations via mentoring and offering individual attention to followers. This study's goal was to ascertain how leadership affected organizational development and transformation within a business.